Rapid investigation of Αlpha-Glucosidase inhibitory activity of Psychotria Malayana Jack leaf using infrared fingerprinting - Nipun, Tanzina Sharmin; Khatib, Alfi; Ahmed, Qamar Uddin; Redzwan, Irna Elina; Ibrahim, Zalikha (2020)
Background: Psychotria malayana Jack is the plant belongs to Rubiaceae family and known in Malaysia as “meroyan sakat/salung”. The analytical approach used in the quality control of Psychotria malayana leaves has not been developed yet. Objectives: Therefore, this research was aimed to evaluate the α-glucosidase inhibitory activity of Psychotria malayana Jack leave extracts in correlation to its Fourier transform infrared spectroscopy (FT-IR) fingerprint, utilizing orthogonal partial least square. Methodology: The dried extracts prepared by sonication of different solvents ratios of methanol-water (0, 25, 50, 75, and 100% v/v), were evaluated for the α-glucosidase inhibitory activity and analyzed via infrared spectroscopy. Multivariate data analysis was done through correlating the bioactivity and infrared spectra of every extract using orthogonal partial least square (OPLS) method. Results: The 100% methanol extract of the leave is more effective against α-glucosidase activity. The loading plot from multivariate data analysis identified several functional groups which actively induced α- -glucosidase inhibitory activity. Discussion and Conclusion: The results of the present study developed the FT-IR spectrum profile for the medicinally important plant Psychotria malayana Jack that further confirms its medicinal values. Therefore, Psychotria malayana Jack leaves extract is medicinally potent that assist to develop this plant as an alternative anti-diabetic natural plant-based medicine.